Spectrum of Biochemical Alterations in Patients with Covid-19 - Zarrin Khaliq Chaudari, Muhammad Yaseen, Maria Sarfraz, Maleeha Tahir Butt, Madeeha Jadoon, Sofia Shoukat (Pakistan Journal of Medical & Health Sciences, 2023)
Background and objective: Millions of people worldwide have died from COVID-19, which has caused the failure of the lungs and other organs. The research assessed biochemical anomalies in COVID-19 patients to comprehend the illness and its effect better. Study Design: Retrospective longitudinal cohort analysis Place of study: ABWA Medical College Faisalabad Methods: A total of 150 adult patients (n=150) who tested positive for COVID-19 via RT-PCR were included in the study. A Roche Diagnostics Cobas C501 used spectrophotometry to measure calcium, magnesium, phosphate, lactate dehydrogenase (LDH), urea, creatinine, ferritin, and chloride in the blood. A NOVA electrolytic analyzer used Ion-selective electrodes to measure sodium, chloride, potassium, and bicarbonate. Results: In the study, 33.6% of patients had elevated urea levels, and 22.4% had elevated creatinine levels. Furthermore, 88.8% of patients had elevated ferritin levels, and 93.5% had elevated LDH levels. After 44 weeks, there was a drop in sodium-containing electrolytes, with 9% of patients experiencing a decrease in sodium, 22.4% in potassium, 53.3% in bicarbonate, 48.6% in calcium, and 23.4% in phosphorus. These changes in electrolyte levels suggest a long-term trend in electrolyte depletion among the patient population. There was no significant difference in biochemical anomalies between age groups (p > 0.05). Conclusion: These results suggest that COVID-19 patients have lung illness and multi-organ involvement, which should be considered when managing these patients. These biochemical alterations warrant careful monitoring for organ failure by healthcare practitioners. More study is required to comprehend the processes causing these biochemical anomalies in COVID-19 patients. Keywords: Covid-19, Biochemical alterations, Outcomes